Behavioural adaptation of Malay families and housing modification of terrace houses in Malaysia - Abdul Rahim, Zaiton; Hashim, Ahmad Hariza (2011)
This paper examines the behavioural adaptation of Malay families living in terrace houses with regards to the activity system, privacy and social interaction among Malay families and terrace housing modification. The study uses case studies of 11 Malay families living in the three-bedroom two-storey terrace houses in two urban locations in Malaysia. Findings indicate that behavioural adaptation resulted in changes in some aspects of the Malay culture and housing modifications provided a more supportive living environment but have adverse effects on individual family and housing community due to the constraints of the terrace housing design.